Bilateral acute angle closure glaucoma associated with hydrochlorothiazide-induced hyponatraemia. (4th December 2014) - Chen, Sylvia H; Karanjia, Rustum; Chevrier, Robert L; Marshall, David H
Abstract : We report a case of a 67-year-old woman presenting with bilateral acute angle closure. On investigation, she was found to have bilateral ciliary effusions and profound hyponatraemia. Her effusions resolved with the cessation of hydrochlorothiazide and normalisation of her blood sodium levels by fluid restriction. This case displays a novel association of hyponatraemia as a possible mechanism for the development of bilateral acute angle closure.